Policies of retail sector of India and other selected countries - Subhadip Mukherjee (UTMS Journal of Economics, 2011)
The retail sector is one of the fastest growing sectors in India. Before 1991, the retail sector was mainly unorganized and fragmented. The rapid growth of the organized retail sector has resulted in the decreasing sales of unorganized retail outlets. Along with that, the traditional unorganized retailers were lagging behind in the context of promotional strategies. This study intends to examine the government policies of different countries including India regarding the unorganized and organized retail sector. The present study examines whether the government provides a tight legal framework along with economic support to the small and unorganized retailers to sustain in this big fight. The study concludes that in the environment of intense competition, governments of different countries (including India) had helped small as well as big domestic retail chains through formulating appropriate policies over time. The governments had helped domestic retail chains by providing capital support and/or formulating strict legislations to restrict entry of foreign retailers in their respective countries. In India, all the regulations regarding retail sector is still in state level and is being influenced by the existing political parties of different states. Thus, it varies across states and their impacts are also heterogeneous.
Keywords: L81; O33; 330; retail sector development plan; vendor managed inventory; local chains; transnational corporation; regulatory framework.